The Pretreatment Controlling Nutritional Status Score in Ovarian Cancer: Influence on Prognosis, Surgical Outcome, and Postoperative Complication Rate - Bekos, Christine; Grimm, Christoph; Gensthaler, Lisa; Bartl, Thomas; Reinthaller, Alexander; Schwameis, Richard; Polterauer, Stephan (Geburtshilfe und Frauenheilkunde, 2022)
Introduction The Controlling Nutritional (CONUT) Status score is an established predictor of impaired prognosis in patients with solid tumors. The aim of this study was to investigate the prognostic value of the CONUT score for overall survival and perioperative complication rates in patients with epithelial ovarian cancer.Patients In this retrospective study we assessed the data of 337 consecutive patients with ovarian cancer. The CONUT score was associated with surgical outcome, postoperative complications and clinicopathological parameters. We used univariate log-rank test and multivariable Cox regression models to evaluate the association between pretreatment CONUT scores and survival.Results A low CONUT score (0 – 2) was associated with an early FIGO stage (p = 0.004), complete tumor resection (p < 0.001), less neoadjuvant chemotherapy (p = 0.017) and other histologies than serous cystadenocarcinoma (p = 0.006). Postoperative complications were observed in 51.4% and 60.5% of patients with a CONUT score of 0 – 2 and a score > 2, respectively (p = 0.161). A shorter overall survival was observed in patients with a CONUT score > 2 compared to patients with a low CONUT score, with 5-year overall survival rates of 31.5% and 58.7%, respectively (p < 0.001). In multivariable analysis, both advanced age (p < 0.001) and FIGO stage (p < 0.001), residual disease (p < 0.001) and a high CONUT score (p = 0.048) were independently associated with unfavorable overall survival.Conclusion Pretreatment CONUT score is an independent prognostic marker for overall survival and associated with successful surgery. Patients with a high CONUT score might benefit from pretreatment nutritional intervention.
Keywords: ovarian cancer; ovarian neoplasms; malabsorption syndromes; postoperative complications